Pengaruh Struktur Organisasi dan Budaya Organisasi terhadap Kinerja Karyawan PT Indah Kiat Pulp & Paper Tbk - Rismawati Rismawati; Yupita Asmul Fauziah; Nayla Fitri Anjani; Rafli Pahlevi; Icha Septiani Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of organizational structure and organizational culture on employee performance at PT Indah Kiat Pulp & Paper Tbk. The research uses a quantitative approach with a survey method involving 85 employees as respondents. Data collection techniques were carried out through questionnaires, interviews, and documentation studies. Data analysis used multiple linear regression methods. The results of the study show that the organizational structure and organizational culture partially or simultaneously have a positive and significant effect on employee performance with a contribution of 68.3%. A clear organizational structure with proper division of tasks and an organizational culture that supports innovation and collaboration has been proven to improve employee performance. This research provides implications for management to maintain an effective organizational structure and strengthen a positive organizational culture in managing human resources in the company.